Teachers’ views towards, and practices in the teaching of mother tongue in Uganda: an ethnographic view - Ssentanda, Medadi E; Asiimwe, Allen (Stellenbosch Papers in Linguistics Plus, 2023)
In this paper, we discuss teachers’ views and related classroom practices of teaching the mother tongue, (MT) Luganda as a subject, as observed in rural classrooms in central Uganda. The challenges observed arise from the lack of and, in some cases, limited training of teachers in MT teaching. Also, there is a disjointed approach to the teaching of Luganda and English, languages to which learners are simultaneously introduced when they first learn to read. The disjointed approach to the teaching of Luganda and English brings about the problem of letter-naming when teaching the two languages. In addition, the overrepresentation of the Luganda orthography regarding the use of /r/ and /l/ as though they are phonemes affects the quick mastery of writing skills in Luganda. The paper demonstrates how teachers go about the teaching of the MT (Luganda) and how these difficulties affect language teaching in rural schools in two districts in Uganda. The paper ends with a discussion on what can be done to overcome these challenges with implications on teacher-education.